Percy Jackson$1 (Bs Greek Gods /s - Riordan, Rick; Rocco, John (Los Angeles : Disney-Hyperion, 2014)
Percy Jackson, demigod son of Poseidon, retells the stories of the Greek gods with wit, sarcasm, and modern humor, providing background for the heroes of Olympus.
Illustrated by John Rocco.
Keywords: Mythology, Greek -- Juvenile literature; Gods, Greek -- Juvenile literature